The sound absorption coefficient and noise reduction coefficient of rice husk silica - Tan, Ke Wei (2020)
This paper presents the acoustical behavior of rice husk silica samples in various composition and thickness by using epoxy and methyl ethyl ketone peroxide (MEKP) as binder. Rice husk is one of agriculture waste materials that can be obtained in a large quantity which have the potential in the application of sound absorber. Rice husk silica samples were fabricated in various composition and thickness by using epoxy and methyl ethyl ketone peroxide (MEKP) as binder. Impedance tube testing and physical test were conducted to obtain the properties of rice husk silica. The testing results found that specimens with higher composition of rice husk silica and using MEKP as binder have the lowest density, highest porosity and give a better sound absorption coefficient. The increment of thickness can produce a greater sound absorption at lower frequency. The results also demonstrate 20 mm is the best thickness for a better noise reduction coefficient.